2022
DOI: 10.31635/ccschem.021.202100968
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Bright Mechanoluminescence in a Hydrogen-Bonded Organic Framework by Polar Molecular Rotor Incorporation

Abstract: Luminescent hydrogen-bonded organic frameworks (HOFs) have attracted increasing attention due to the corresponding luminescence readily enables visualization of structural dynamics. HOFs with the mechanoluminescence (ML) property, which can emit light without photon excitation, are greatly attractive for advanced applications but have not been reported so far. Herein, we report the first example of a ML-active flexible HOF with permanent porosity, named 8PCOM, which is assembled from polar molecular rotors wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Chi and coworkers reported the first flexible HOFs with mechanoluminescence, named 8PCOM. [ 24 ] The ML phenomenon appeared in polar organic molecules with lower symmetric structures. A dynamic polar molecule, TPE‐4PCOM (5), acted as the building block for mechanoluminescence‐active flexible HOFs ( Figure a).…”
Section: Luminescent Hydrogen‐bonded Organic Frameworkmentioning
confidence: 99%
“…12) in 2021 and prepared six crystals from different solvents (8PCOM-DCM, 8PCOM-TOL, 8PCOM-DMSO, 8PCOM-DMF, 8PCOM-ACT, and 8PCOM-MeOH) to investigate the mechanoluminescence (ML) of crystals. 77 Each TPE-4PCOM molecule interacts with four adjacent ones via many H-bond interactions, and they extend to form a porous single layer. Many layers further stack together to construct a 3D porous framework with 1D channels.…”
Section: Tunable Luminescence By the Guest Stacking Type And Mechanic...mentioning
confidence: 99%